Evaluation of retail services: A developed vs emerging markets perspective - Sharma, Piyush; Luk, S.T.; Chen, I.S. (American Marketing Association (AMA), 2012)
Customers from different countries have varied experiences and expectations due to diverse socioeconomic, cultural, and environmental factors (Douglas and Craig 2006). They also differ in their service experience in terms of customer perceived value, customer satisfaction, and perceived service quality (Brady et al. 2005). However, prior research on the evaluation of retail services focuses mostly on the shoppers from developed markets with little attention to shoppers from emerging markets such as China (Uncles 2010) and India (Sengupta 2008).